Binder and preparation method thereof, negative pole piece, battery monomer, battery and electric device

By preparing binders containing polyethylene glycol, carboxyl and cyanopolymers, the problems of polyethylene glycol dissolution and swelling in lithium-ion batteries are solved, and stable application and energy density improvement are achieved in the negative electrode.

CN119315031APending Publication Date: 2025-01-14CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310861896.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-13
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Polyethylene glycol is completely dissolved in the electrolyte of lithium-ion batteries and has a high swelling degree, which limits its application in the negative electrode.

Method used

By preparing a binder, it contains 3% to 6.4% by weight of polyethylene glycol, 2.45% to 18% by weight of carboxyl group-containing polymer, 0.61% to 5% by weight of cyano group-containing polymer and 0-9% by weight of weight of % by weight of carboxyl group-containing polymer, 0.61% to 5% by weight of cyano group-containing polymer and 0-9% by weight of weight of The ester-containing polymer is made by physical blending to prepare a stable binder, and the dissolution and swelling problems in the lithium-ion battery electrolyte are adjusted.

Benefits of technology

The binder is insoluble in the lithium-ion battery electrolyte, and the swelling degree is controlled within a suitable range, which improves the bonding force and energy density of the negative electrode, and meets the later application requirements of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315031A_ABST
    Figure CN119315031A_ABST
Patent Text Reader

Abstract

The invention provides a binder and a preparation method thereof, a negative pole piece, a battery monomer, a battery and an electric device, and belongs to the technical field of batteries. The binder comprises 3 wt% to 6.4 wt% of polyethylene glycol, 2.45 wt% to 18 wt% of a polymer containing carboxyl groups and 0.61 wt% to 5 wt% of a polymer containing cyano groups. The carboxyl-containing polymer provides carboxyl, so that the binding power of the binding agent can be improved, the binding agent and hydroxyl of polyethylene glycol form hydrogen bonds, the problem of dissolution of polyethylene glycol in an electrolyte of the lithium ion battery is solved, the cyano-containing polymer can adjust the swelling degree of polyethylene glycol in the electrolyte of the lithium ion battery, and the binding force of the binding agent is improved. Therefore, the later application requirement of the binder in the electrolyte of the lithium ion battery is met. According to the binder disclosed by the invention, the problems of dissolution and swelling of the binder in an electrolyte of the lithium ion battery are adjusted by controlling the proportion of the polyethylene glycol, the carboxyl-containing polymer and the cyano-containing polymer, so that the binder can be applied to a negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a binder and a preparation method thereof, a negative electrode sheet, a battery cell, a battery and an electrical device. Background Art

[0002] Polyethylene glycol contains abundant ether bonds, but it is completely soluble in the electrolyte and has a high swelling degree, which limits its application in negative electrodes. Summary of the invention

[0003] In view of the above problems, the present application provides a binder and a preparation method thereof, a negative electrode plate, a battery cell, a battery and an electrical device, which can improve the dissolution and swelling problems of polyethylene glycol in the electrolyte of a lithium-ion battery, so that it can be used as a binder for the negative electrode active material layer.

[0004] In a first aspect, the present application provides a binder comprising: 3wt% to 6.4wt% polyethylene glycol, 2.45wt% to 18wt% carboxyl-containing polymer, 0.61wt% to 5wt% cyano-containing polymer, 0 to 9wt% ester-containing polymer and the remainder solvent.

[0005] In the technical solution of the embodiment of the present application, the carboxyl-containing polymer provides carboxyl groups, which can improve the bonding force of the binder and form hydrogen bonds with the hydroxyl groups of polyethylene glycol, thereby improving the dissolution of polyethylene glycol in the electrolyte of the lithium-ion battery. The cyano-containing polymer can adjust the swelling degree of polyethylene glycol in the electrolyte of the lithium-ion battery, thereby meeting the later application requirements of the binder in the electrolyte of the lithium-ion battery. The binder of the present application adjusts the dissolution and swelling problems of the binder in the electrolyte of the lithium-ion battery by controlling the proportion of polyethylene glycol, the carboxyl-containing polymer and the cyano-containing polymer, so that the binder can be applied to the negative electrode.

[0006] In some embodiments, the binder includes 3wt% to 6.2wt% polyethylene glycol, 2.5wt% to 18wt% carboxyl-containing polymer, 0.63wt% to 5wt% cyano-containing polymer, 0 to 9wt% ester-containing polymer and the remainder of solvent. When the binder includes 3wt% to 6.2wt% polyethylene glycol, 2.5wt% to 18wt% carboxyl-containing polymer and 0.63wt% to 5wt% cyano-containing polymer, the polyethylene glycol is completely insoluble in the electrolyte of the lithium ion battery, and the swelling degree in the electrolyte of the lithium ion battery is ≤230%.

[0007] In some embodiments, the weight average molecular weight of the polyethylene glycol is ≥ 500,000. When the weight average molecular weight of the polyethylene glycol is ≥ 500,000, the amount of binder added to the negative electrode does not need to be too much, thereby improving the energy density of the battery cell.

[0008] In some embodiments, the carboxyl-containing polymer includes polyacrylic acid and / or maleic acid-acrylic acid copolymer. Polyacrylic acid and maleic acid-acrylic acid copolymer can provide carboxyl groups to improve the bonding strength of the binder, and form hydrogen bonds with the hydroxyl groups of polyethylene glycol to improve the solubility of polyethylene glycol in the electrolyte of lithium-ion batteries.

[0009] In some embodiments, the cyano group-containing polymer includes polyacrylonitrile, which can adjust the swelling degree of polyethylene glycol in the electrolyte of the lithium-ion battery, thereby meeting the later application requirements of the binder in the electrolyte of the lithium-ion battery.

[0010] In some embodiments, the binder includes 1.23 wt% to 9 wt% of an ester-containing polymer. The ester-containing polymer can provide a flexible segment, adjust the softness of the binder after curing, and improve the affinity with graphite, which is beneficial for later application in the negative electrode.

[0011] In some embodiments, the ester-containing polymer includes at least one of polyacrylate, polyethylene methyl oxalate, or polycarbonate. Polyacrylate, polyethylene methyl oxalate, and polycarbonate can provide flexible segments, adjust the softness of the binder after curing, and improve the affinity with graphite, which is beneficial for later application in the negative electrode.

[0012] In some embodiments, the solubility of the binder in the electrolyte solvent of the lithium ion battery is ≤215%, and / or the solubility of the binder in the electrolyte of the lithium ion battery is ≤230%.

[0013] In a second aspect, the present application provides a method for preparing the binder in the above-mentioned embodiment, which comprises: separately preparing a first aqueous phase solution containing a carboxyl-containing polymer and an oil phase solution containing a cyano-containing polymer, mixing and dispersing the first aqueous phase solution and the oil phase solution to form a dispersion, and mixing the dispersion with a second aqueous phase solution containing polyethylene glycol to prepare a binder.

[0014] In the technical solution of the embodiment of the present application, the preparation method of the adhesive of the present application can obtain a stable adhesive by only using a physical blending method, and the preparation process is simple.

[0015] In some embodiments, the step of mixing and dispersing the first aqueous phase solution and the oil phase solution comprises: emulsifying and dispersing the first aqueous phase solution and the oil phase solution at a speed of 1000 r / min to 5000 r / min to obtain a dispersion. High-speed emulsification and dispersion is conducive to uniform mixing of the first aqueous phase solution and the oil phase solution to obtain a uniform dispersion.

[0016] In some embodiments, the step of mixing the dispersion and the second aqueous phase solution containing polyethylene glycol comprises: adding the dispersion to the second aqueous phase solution dropwise at a rate of ≤5 g / h. Controlling the rate of adding the dispersion to the second aqueous phase solution is beneficial to reducing bubbles in the binder.

[0017] In some embodiments, the ester-containing polymer>0 wt%, and the oil phase solution contains the ester-containing polymer. When the ester-containing polymer>0 wt%, the ester-containing polymer is added to the oil phase solution.

[0018] In a third aspect, the present application provides a battery cell, which includes an electrolyte and the negative electrode plate in the above embodiment.

[0019] Optionally, the battery cells include lithium-ion battery cells.

[0020] In some embodiments, the electrolyte includes ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, and lithium hexafluorophosphate.

[0021] In a fourth aspect, the present application provides a battery, which includes the battery cell in the above embodiment.

[0022] In a fifth aspect, the present application provides an electrical device, which includes the battery cell or battery in the above embodiment, and the battery cell or battery is used to provide electrical energy.

[0023] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:

[0025] Figure 1 A schematic diagram of the structure of a vehicle according to some embodiments of the present application;

[0026] Figure 2 A schematic diagram of the exploded structure of a battery according to some embodiments of the present application;

[0027] Figure 3 A schematic diagram of the exploded structure of a battery cell according to some embodiments of the present application;

[0028] Figure 4This is a schematic diagram of the test of the softness of the electrode in Test Example 2 of this application.

[0029] The reference numerals in the specific implementation manner are as follows:

[0030] 1000-Vehicle; 100-Battery; 200-Controller; 300-Motor;

[0031] 10-box; 11-first part; 12-second part;

[0032] 20 - battery cell; 21 - end cover; 22 - housing; 23 - electrode assembly. DETAILED DESCRIPTION

[0033] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0035] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0037] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0038] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0039] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.

[0040] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0041] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.

[0042] Ethers have excellent kinetics and are widely used in solid-state batteries and lithium-sulfur batteries. The electrochemical potential window of lithium-ion batteries can be as high as 4.3V, while the electrochemical potential window of ethers can only reach about 3.8V, which means that ethers cannot be used directly in the electrolyte or positive electrode of lithium-ion batteries. You can try to solidify ethers on the negative electrode for use.

[0043] Polyethylene glycol contains abundant ether bonds and has excellent dynamics, but it is completely soluble in the electrolyte and has a high swelling degree, which limits its application in negative electrodes.

[0044] Based on the above considerations, in order to improve the dissolution and swelling problems of polyethylene glycol in the electrolyte of lithium-ion batteries, a binder is prepared by compounding polyethylene glycol, a carboxyl-containing polymer and a cyano-containing polymer in a specific ratio. The carboxyl-containing polymer provides carboxyl groups, which can improve the bonding strength of the binder and form hydrogen bonds with the hydroxyl groups of polyethylene glycol to improve the dissolution problem of polyethylene glycol in the electrolyte of lithium-ion batteries. The cyano-containing polymer can adjust the swelling degree of polyethylene glycol in the electrolyte of lithium-ion batteries, thereby meeting the later application requirements of the binder in the electrolyte of lithium-ion batteries, so that the binder can be applied to the negative electrode.

[0045] The battery mentioned in the embodiments of the present application refers to a single physical module including multiple battery cells to provide higher voltage and capacity. The battery generally includes a battery box for packaging multiple battery cells, and the battery box can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells.

[0046] Each battery cell is a secondary battery; it can be a lithium-ion battery or a lithium-sulfur battery, but is not limited thereto. The battery cell can be cylindrical, flat, rectangular or in other shapes. Battery cells are generally divided into three types according to the packaging method: cylindrical battery cells, square battery cells and soft-pack battery cells.

[0047] The battery cell includes an electrode assembly and an electrolyte. The electrode assembly is composed of a positive electrode sheet, a negative electrode sheet and a separator. The battery cell mainly relies on the movement of metal ions between the positive electrode sheet and the negative electrode sheet to work. The positive electrode sheet includes a positive electrode collector and a positive electrode active material layer. The positive electrode active material layer is coated on the surface of the positive electrode collector. The positive electrode collector not coated with the positive electrode active material layer protrudes from the positive electrode collector coated with the positive electrode active material layer. The positive electrode collector not coated with the positive electrode active material layer serves as the positive electrode tab. Taking lithium-ion batteries as an example, the material of the positive electrode collector can be aluminum, and the positive electrode active material can be lithium cobalt oxide, lithium iron phosphate, ternary lithium or lithium manganese oxide. The negative electrode sheet includes a negative electrode collector and a negative electrode active material layer. The negative electrode active material layer is coated on the surface of the negative electrode collector. The negative electrode collector not coated with the negative electrode active material layer protrudes from the negative electrode collector coated with the negative electrode active material layer. The negative electrode collector not coated with the negative electrode active material layer serves as the negative electrode tab. The material of the negative electrode collector can be copper. In order to ensure that a large current does not melt, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The material of the isolation film can be polypropylene (PP) or polyethylene (PE). In addition, the electrode assembly can be a winding structure or a laminated structure, and the embodiments of the present application are not limited thereto.

[0048] The battery cell also includes a current collecting component, which is used to electrically connect the tabs and electrode terminals of the battery cell to transmit electrical energy from the electrode assembly to the electrode terminals and then to the outside of the battery cell through the electrode terminals; multiple battery cells are electrically connected through a current collecting component to achieve series, parallel or mixed connection of multiple battery cells.

[0049] The battery also includes a sampling terminal and a battery management system. The sampling terminal is connected to the busbar to collect information about the battery cells, such as voltage or temperature, etc. The sampling terminal transmits the collected information about the battery cells to the battery management system. When the battery management system detects that the information about the battery cells exceeds the normal range, it will limit the output power of the battery to achieve safety protection.

[0050] It can be understood that the electrical devices used by the batteries described in the embodiments of the present application can be in various forms, for example, mobile phones, portable devices, laptops, battery vehicles, electric cars, ships, spacecraft, electric toys and electric tools, etc. For example, spacecraft include airplanes, rockets, space shuttles and spacecraft, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.

[0051] The battery cells and batteries described in the embodiments of the present application are not limited to the electrical devices described above, but can also be applied to all electrical devices using battery cells and batteries. However, for the sake of simplicity, the following embodiments are described using electric vehicles as examples.

[0052] See also Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle provided for some embodiments of the present application. Vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A battery 100 is provided inside the vehicle 1000, and the battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The battery 100 may be used to power the vehicle 1000, for example, the battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 200 and a motor 300, and the controller 200 is used to control the battery 100 to power the motor 300, for example, for starting, navigating and driving the vehicle 1000.

[0053] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0054] Please refer to Figure 2 , Figure 2 An exploded diagram of a battery provided for some embodiments of the present application. The battery 100 includes a housing 10 and a battery cell 20, and the battery cell 20 is contained in the housing 10. Among them, the housing 10 is used to provide a storage space for the battery cell 20, and the housing 10 can adopt a variety of structures. In some embodiments, the housing 10 may include a first part 11 and a second part 12, and the first part 11 and the second part 12 cover each other, and the first part 11 and the second part 12 jointly define a storage space for accommodating the battery cell 20. The second part 12 may be a hollow structure with one end open, and the first part 11 may be a plate-like structure, and the first part 11 covers the open side of the second part 12, so that the first part 11 and the second part 12 jointly define a storage space; the first part 11 and the second part 12 may also be hollow structures with one side open, and the open side of the first part 11 covers the open side of the second part 12. Of course, the housing 10 formed by the first part 11 and the second part 12 may be in a variety of shapes, such as a cylinder, a cuboid, etc.

[0055] In the battery 100, there may be multiple battery cells 20, and the multiple battery cells 20 may be connected in series, in parallel, or in a mixed connection. A mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 may be directly connected in series, in parallel, or in a mixed connection, and then the whole formed by the multiple battery cells 20 is accommodated in the box 10; of course, the battery 100 may also be a battery module formed by connecting multiple battery cells 20 in series, in parallel, or in a mixed connection, and then the multiple battery modules are connected in series, in parallel, or in a mixed connection to form a whole, and accommodated in the box 10. The battery 100 may also include other structures, for example, the battery 100 may also include a busbar component for realizing electrical connection between the multiple battery cells 20.

[0056] Each battery cell 20 is a secondary battery, which may be a lithium-ion battery, a lithium-sulfur battery, a sodium-ion battery or a magnesium-ion battery, but is not limited thereto. The battery cell 20 may be cylindrical, flat, rectangular or in other shapes.

[0057] Please refer to Figure 3 , Figure 3 The first battery cell 20 is a schematic diagram of the decomposed structure of some embodiments of the present application. The battery cell 20 refers to the smallest unit that constitutes the battery. Figure 3 The battery cell 20 includes an end cover 21, a shell 22, an electrode assembly 23 and other functional components.

[0058] The end cap 21 refers to a component that covers the opening of the shell 22 to isolate the internal environment of the battery cell 20 from the external environment. Without limitation, the shape of the end cap 21 can be adapted to the shape of the shell 22 to match the shell 22. Optionally, the end cap 21 can be made of a material with a certain hardness and strength (such as aluminum alloy), so that the end cap 21 is not easily deformed when squeezed and collided, so that the battery cell 20 can have a higher structural strength and the safety performance can also be improved. Functional components such as electrode terminals can be provided on the end cap 21. The electrode terminal can be used to electrically connect to the electrode assembly 23 for outputting or inputting electrical energy of the battery cell 20. In some embodiments, the end cap 21 can also be provided with a pressure relief mechanism for releasing the internal pressure when the internal pressure or temperature of the battery cell 20 reaches a threshold. The material of the end cap 21 can also be a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiments of the present application do not impose special restrictions on this. In some embodiments, an insulating member may be provided inside the end cap 21, and the insulating member may be used to isolate the electrical connection components in the housing 22 from the end cap 21 to reduce the risk of short circuit. For example, the insulating member may be plastic, rubber, or the like.

[0059] The shell 22 is a component used to cooperate with the end cap 21 to form the internal environment of the battery cell 20, wherein the formed internal environment can be used to accommodate the electrode assembly 23, the electrolyte and other components. The shell 22 and the end cap 21 can be independent components, and an opening can be set on the shell 22, and the internal environment of the battery cell 20 is formed by covering the opening with the end cap 21 at the opening. Without limitation, the end cap 21 and the shell 22 can also be integrated. Specifically, the end cap 21 and the shell 22 can form a common connection surface before other components are put into the shell, and when the interior of the shell 22 needs to be encapsulated, the end cap 21 covers the shell 22. The shell 22 can be of various shapes and sizes, such as a rectangular parallelepiped, a cylindrical shape, a hexagonal prism, etc. Specifically, the shape of the shell 22 can be determined according to the specific shape and size of the electrode assembly 23. The material of the shell 22 can be various, such as copper, iron, aluminum, stainless steel, aluminum alloy, plastic, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0060] The electrode assembly 23 is a component in the battery cell 20 where electrochemical reactions occur. One or more electrode assemblies 23 may be included in the housing 22. The electrode assembly 23 is mainly formed by winding or stacking positive and negative electrode sheets, and a separator is usually provided between the positive and negative electrode sheets. The parts of the positive and negative electrode sheets with active materials constitute the main body of the electrode assembly, and the parts of the positive and negative electrode sheets without active materials each constitute a lug. The positive and negative electrode lugs may be located together at one end of the main body or at both ends of the main body, respectively. During the charge and discharge process of the battery, the positive and negative electrode active materials react with the electrolyte, and the lugs connect the electrode terminals to form a current loop.

[0061] According to some embodiments of the present application, the present application provides a binder comprising: 3wt% to 6.4wt% polyethylene glycol, 2.45wt% to 18wt% carboxyl-containing polymer, 0.61wt% to 5wt% cyanide-containing polymer, 0 to 9wt% ester-containing polymer and the remainder solvent.

[0062] The carboxyl-containing polymer refers to a polymer containing a carboxyl functional group in the molecule, and the carboxyl functional group can be located at the head or the end or on the side chain.

[0063] The cyano-containing polymer refers to a polymer containing a cyano functional group in the molecule, and the cyano functional group can be located at the head, terminal or on a side chain.

[0064] The ester-containing polymer refers to a polymer containing an ester functional group in the molecule, and the ester functional group can be located at the head or the end or on the side chain.

[0065] As an example, the binder may include 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5.8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt% or 6.4wt% polyethylene glycol, 2.45wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4 %. .5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt%, 15wt%, 15.5wt%, 16wt%, 16.5wt%, 17wt%, 17.5wt% or 18wt% of a polymer containing a carboxyl group, 0.61wt%, 0.7wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt% of a polymer containing a cyano group, 0-9wt% of a polymer containing an ester group and the remainder being a solvent.

[0066] The solvent includes an aqueous solvent and an oily solvent, wherein the aqueous solvent includes deionized water, and the oily solvent includes tetrahydrofuran.

[0067] Optionally, the mass ratio of the aqueous solvent to the oily solvent may be any ratio.

[0068] Optionally, the mass ratio of the aqueous solvent to the oily solvent is 6-8:2-4.

[0069] The carboxyl-containing polymer provides carboxyl groups, which can improve the bonding force of the binder and form hydrogen bonds with the hydroxyl groups of polyethylene glycol, thereby improving the dissolution of polyethylene glycol in the electrolyte of the lithium-ion battery. The cyano-containing polymer can adjust the swelling degree of polyethylene glycol in the electrolyte of the lithium-ion battery, thereby meeting the later application requirements of the binder in the electrolyte of the lithium-ion battery. The binder of the present application adjusts the dissolution and swelling problems of the binder in the electrolyte of the lithium-ion battery by controlling the proportion of polyethylene glycol, the carboxyl-containing polymer and the cyano-containing polymer, so that the binder can be applied to the negative electrode.

[0070] According to some embodiments of the present application, optionally, the binder includes 3wt% to 6.2wt% polyethylene glycol, 2.5wt% to 18wt% carboxyl-containing polymer, 0.63wt% to 5wt% cyano-containing polymer, 0 to 9wt% ester-containing polymer and the remainder solvent.

[0071] When the binder includes 3wt% to 6.2wt% of polyethylene glycol, 2.5wt% to 18wt% of a carboxyl-containing polymer and 0.63wt% to 5wt% of a cyano-containing polymer, the polyethylene glycol is completely insoluble in the electrolyte of the lithium ion battery and has a swelling degree of ≤230% in the electrolyte of the lithium ion battery.

[0072] According to some embodiments of the present application, optionally, the weight average molecular weight of the polyethylene glycol is ≥ 500,000.

[0073] As an example, the weight average molecular weight of polyethylene glycol can be 0.5 million, 0.6 million, 0.7 million, 0.8 million, 0.9 million, 1 million, 1.1 million, 1.2 million, 1.3 million, 1.4 million, or 1.5 million.

[0074] The weight average molecular weight is the molecular weight averaged over a unit weight, has a well-known definition in the art, and can be measured by testing instruments and methods well-known in the art, for example, reference can be made to the national standard GB / T 21863-2008 gel permeation chromatography.

[0075] When the weight average molecular weight of polyethylene glycol is ≥ 500,000, the amount of binder added to the negative electrode does not need to be too much, thereby improving the energy density of the battery cell.

[0076] Optionally, the weight average molecular weight of polyethylene glycol is 500,000 to 1.5 million.

[0077] The swelling degree of polyethylene glycol increases with the increase of molecular weight. In order to meet the later application requirements of the binder in the electrolyte of lithium-ion batteries, the weight average molecular weight of polyethylene glycol is controlled within 1.5 million.

[0078] According to some embodiments of the present application, optionally, the carboxyl group-containing polymer includes polyacrylic acid and / or maleic acid-acrylic acid copolymer.

[0079] As examples, the carboxyl group-containing polymer may be polyacrylic acid alone, or a maleic acid-acrylic acid copolymer alone, or a mixture of polyacrylic acid and a maleic acid-acrylic acid copolymer.

[0080] Polyacrylic acid and maleic acid-acrylic acid copolymer can provide carboxyl groups to improve the bonding strength of the binder, and form hydrogen bonds with the hydroxyl groups of polyethylene glycol to improve the solubility problem of polyethylene glycol in the electrolyte of lithium-ion batteries.

[0081] According to some embodiments of the present application, optionally, the cyano group-containing polymer includes polyacrylonitrile.

[0082] Polyacrylonitrile can adjust the swelling degree of polyethylene glycol in the electrolyte of lithium-ion batteries, thereby meeting the later application requirements of the binder in the electrolyte of lithium-ion batteries.

[0083] According to some embodiments of the present application, optionally, the binder includes 1.23 wt % to 9 wt % of an ester-containing polymer.

[0084] As an example, the binder may include 1.23 wt%, 1.3 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt% or 9 wt% of an ester-containing polymer,

[0085] Ester-containing polymers can provide flexible segments, adjust the softness of the binder after curing, and at the same time improve the affinity with graphite, which is beneficial for later application in the negative electrode.

[0086] According to some embodiments of the present application, optionally, the ester-containing polymer includes at least one of polyacrylate, polyethylene glycol ether or polycarbonate.

[0087] As an example, the ester-containing polymer can be a single polyacrylate, or a single polyethylene methyl oxalate, or a single polycarbonate, or a mixture of polyacrylate and polyethylene methyl oxalate, or a mixture of polyethylene methyl oxalate and polycarbonate, or a mixture of polyacrylate and polycarbonate, or a mixture of polyacrylate, polyethylene methyl oxalate and polycarbonate.

[0088] Polyacrylate, polyethylene glycol ether and polycarbonate can provide flexible segments, adjust the softness of the binder after curing, and at the same time improve the affinity with graphite, which is beneficial for later application in the negative electrode.

[0089] According to some embodiments of the present application, the present application also provides a method for preparing the binder in the above embodiments, which comprises: separately preparing a first aqueous phase solution containing a carboxyl-containing polymer and an oil phase solution containing a cyano-containing polymer, mixing and dispersing the first aqueous phase solution and the oil phase solution to form a dispersion, mixing the dispersion and a second aqueous phase solution containing polyethylene glycol to prepare the binder.

[0090] The preparation method of the adhesive of the present application can obtain a stable adhesive by only using a physical blending method, and the preparation process is simple.

[0091] The first aqueous phase solution includes a carboxyl group-containing polymer and an aqueous solvent.

[0092] Optionally, the mass percentage of the carboxyl-containing polymer in the first aqueous phase solution is 1 wt % to 36 wt %.

[0093] Optionally, the aqueous solvent is water, and the water may be distilled water, deionized water, or the like.

[0094] The oil phase solution comprises a cyano group-containing polymer and an oily solvent.

[0095] Optionally, the mass percentage of the cyano group-containing polymer in the oil phase solution is 1 wt% to 25 wt%.

[0096] Optionally, the oily solvent comprises tetrahydrofuran.

[0097] The second aqueous phase solution includes polyethylene glycol and an aqueous solvent.

[0098] Optionally, the mass percentage of polyethylene glycol in the second aqueous phase solution is 1 wt % to 20 wt %.

[0099] According to some embodiments of the present application, optionally, the step of mixing and dispersing the first aqueous phase solution and the oil phase solution includes: emulsifying and dispersing the first aqueous phase solution and the oil phase solution at a rotation speed of 1000 r / min to 5000 r / min to obtain a dispersion.

[0100] As an example, the first aqueous phase solution and the oil phase solution are emulsified and dispersed at a rotation speed of 1000 r / min, 1500 r / min, 2000 r / min, 2500 r / min, 3000 r / min, 3500 r / min, 4000 r / min, 4500 r / min or 5000 r / min to prepare a dispersion.

[0101] High-speed emulsification and dispersion is beneficial to uniformly mix the first aqueous phase solution and the oil phase solution to obtain a uniform phase dispersion.

[0102] According to some embodiments of the present application, optionally, the step of mixing the dispersion and the second aqueous phase solution containing polyethylene glycol includes: adding the dispersion dropwise to the second aqueous phase solution at a dropping rate of ≤5 g / h.

[0103] As an example, the dropwise addition rate of the dispersion into the second aqueous phase solution may be 1 g / h, 2 g / h, 3 g / h, 4 g / h or 5 g / h.

[0104] Controlling the dropping rate of the dispersion into the second aqueous phase solution is beneficial to reducing bubbles in the binder.

[0105] Optionally, the dispersion is added dropwise to the second aqueous phase solution at a dropping rate of 1 g / h to 5 g / h.

[0106] Alternatively, the dispersion is added dropwise to the second aqueous phase solution under stirring.

[0107] Optionally, the dispersion is added dropwise into the second aqueous phase solution at 5°C to 35°C.

[0108] According to some embodiments of the present application, optionally, the ester-containing polymer>0wt%, and the oil phase solution contains the ester-containing polymer.

[0109] When the ester group-containing polymer is greater than 0 wt %, the ester group-containing polymer is added to the oil phase solution.

[0110] Alternatively, when the ester group-containing polymer is greater than 0 wt %, the oil phase solution comprises the cyano group-containing polymer, the ester group-containing polymer and an oily solvent.

[0111] Optionally, the mass percentage of the ester group-containing polymer in the oil phase solution is 1 wt% to 40 wt%.

[0112] According to some embodiments of the present application, the present application also provides a battery cell, which includes an electrolyte and the negative electrode plate in the above embodiment.

[0113] Optionally, the battery cells include lithium-ion battery cells.

[0114] According to some embodiments of the present application, optionally, the electrolyte includes ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and lithium hexafluorophosphate.

[0115] The following is a further detailed description of an adhesive and a preparation method thereof of the present application in conjunction with embodiments.

[0116] The parameters of the binders of Examples 1 to 15 and Comparative Examples 1 to 4 of the present application are shown in Table 1.

[0117] Table 1 Parameters of the binders of Examples 1 to 15 and Comparative Examples 1 to 4

[0118]

[0119]

[0120] The binders of Examples 1 to 15 and Comparative Examples 1 to 4 were prepared by the following method:

[0121] S1. Preparation of the first aqueous phase solution

[0122] 20 g of polyacrylic acid was dissolved in 100 g of deionized water to prepare a first aqueous phase solution.

[0123] S2. Preparation of oil phase solution

[0124] 10 g of polyacrylate was dissolved in 100 g of tetrahydrofuran to prepare an oil phase solution.

[0125] If the mass percentage of polyacrylate or polycarbonate in the binder is greater than 0wt%, a corresponding mass of polyacrylate or polycarbonate needs to be added to the oil phase solution.

[0126] S3. Preparation of dispersion

[0127] The first aqueous phase solution and the oil phase solution were mixed according to a ratio and placed in a high shear emulsifier. The first aqueous phase solution and the oil phase solution were emulsified and dispersed at a speed of 3000 r / min to obtain a dispersion, which was transferred to a beaker for later use.

[0128] S4, prepare the second aqueous phase solution

[0129] The second aqueous phase solution was prepared by dissolving 10 g of polyethylene glycol in 100 g of deionized water.

[0130] S5. Preparation of binder

[0131] Under stirring at 400 r / min, the prepared dispersion was added dropwise to the second aqueous phase solution at 25° C. according to the proportion, with a dropping rate of 1 g / h.

[0132] Test Example 1

[0133] The adhesives prepared in Examples 1 to 15 and Comparative Examples 1 to 4 were placed in an oven at 70° C. and baked for 12 hours to obtain adhesive films. The dissolution, loss rate and swelling degree of the adhesive films when immersed in electrolyte solvent and electrolyte were measured respectively. The results are shown in Table 2.

[0134] The electrolyte solvent includes 23 wt % of ethylene carbonate, 23 wt % of propylene carbonate, 23 wt % of dimethyl carbonate, 9 wt % of diethyl carbonate and 10 wt % of ethyl methyl carbonate.

[0135] The electrolyte includes an electrolyte solvent and lithium hexafluorophosphate, and the molar concentration of the lithium hexafluorophosphate is 1 mol / L.

[0136] The method for detecting whether the film is dissolved, the loss rate and the swelling degree when immersed in the electrolyte solvent is as follows:

[0137] The adhesives prepared in Examples 1 to 15 and Comparative Examples 1 to 4 were placed in an oven at 70°C and baked for 12 hours to obtain adhesive films, and the mass of the adhesive films was weighed to obtain m1. The adhesive films were respectively immersed in electrolyte solvents and placed in an oven at 60°C and baked for 24 hours, then the adhesive films were taken out, the electrolyte solvent on the surface of the adhesive films was wiped dry, and the color of the electrolyte solvent was carefully observed to see if there was any color change and substance dissolution, and the mass of the adhesive film was weighed to obtain m2, and the swelling was calculated; then the weighed adhesive film was placed in an oven at 120°C and baked for 24 hours, then the adhesive film was taken out, the mass of the adhesive film was weighed to obtain m3, and the loss rate was calculated.

[0138] Swelling degree in electrolyte solvent = m2 / m1*100%;

[0139] Loss rate in electrolyte solvent = (m1-m3) / m1*100%.

[0140] The method for detecting whether the film is dissolved and the swelling degree when immersed in the electrolyte is as follows:

[0141] The adhesives prepared in Examples 1 to 15 and Comparative Examples 1 to 4 were placed in an oven at 70°C and baked for 12 hours to obtain adhesive films, and the mass of the adhesive films was weighed to obtain m1. The adhesive films were respectively immersed in electrolyte and placed in an oven at 60°C and baked for 24 hours. The adhesive films were then taken out, the electrolyte on the surface of the adhesive films was wiped dry, and the color of the electrolyte was carefully observed to see if there was any color change or substance dissolution. The mass of the adhesive film was weighed to obtain m4, and the swelling was calculated.

[0142] Swelling degree in electrolyte = m4 / m1*100%;

[0143] Table 2 Properties of the adhesives obtained in Examples 1 to 15 and Comparative Examples 1 to 4

[0144]

[0145]

[0146] It can be seen from Examples 1 to 9 and 14 to 15 that when the binder includes 3wt% to 6.2wt% polyethylene glycol, 2.5wt% to 18wt% carboxyl-containing polymers, 0.63wt% to 5wt% cyano-containing polymers and 0 to 9wt% ester-containing polymers, the binder is completely insoluble in the electrolyte solvent and electrolyte of the lithium ion battery, and the swelling degree in the electrolyte solvent of the lithium ion battery is ≤215%, and the swelling degree in the electrolyte is ≤230%.

[0147] It can be seen from Examples 10 to 13 that when the binder includes 6.2wt% to 6.4wt% polyethylene glycol, 2.45wt% to 2.5wt% carboxyl-containing polymer, 0.61wt% to 0.63wt% cyano-containing polymer and 0 to 9wt% ester-containing polymer, the binder is partially dissolved in the electrolyte solvent and electrolyte of the lithium ion battery, and the swelling degree in the electrolyte solvent of the lithium ion battery is ≤360%, and the swelling degree in the electrolyte is ≤400%.

[0148] It can be seen from Comparative Examples 1 to 3 that when the carboxyl-containing polymer in the binder is less than 2.45%, the binder is completely dissolved in the electrolyte solvent and the electrolyte.

[0149] It can be seen from Comparative Example 4 that when there is no cyanide-containing polymer in the binder, the swelling degree of the binder in the electrolyte solvent of the lithium-ion battery is as high as 543%, and the swelling degree in the electrolyte is as high as 654%.

[0150] Test Example 2

[0151] The adhesives prepared in Examples 1 to 15 were made into pole pieces, and the softness of the pole pieces is shown in Table 3.

[0152] The test method for the softness of the pole piece is as follows:

[0153] Test tool: rolling needle (diameter: 1mm);

[0154] Test conditions: temperature = 25 ± 1 ° C, relative humidity = 65 ± 5%;

[0155] Test steps: (1) Winding needle: Take the cold pressed electrode, wrap the electrode around the winding needle, and align the part around the winding needle with force, such as Figure 4 As shown;

[0156] (2) Microscope observation: Aim the objective lens at the bent tip, magnify it 100 times, and observe whether there are any cracks.

[0157] Table 3 Softness of the pole pieces obtained in Examples 1 to 15

[0158] project Is there any crack? Example 1 Bending without cracks Example 2 Bending without cracks Example 3 Bending without cracks Example 4 Bend without cracks Example 5 Bend without cracks Example 6 Bend without cracks Example 7 There are obvious cracks in the bend Example 8 Bending without cracks Example 9 Bending without cracks Example 10 Bending without cracks Embodiment 11 Bend without cracks Example 12 Bending without cracks Example 13 Bend without cracks Embodiment 14 Bend without cracks Embodiment 15 Bending without cracks

[0159] By comparing Examples 1 to 6, 8 to 15 with Example 7, it can be seen that there is no ester-containing polymer in Example 7, and the pole piece made of the adhesive has obvious cracks when bent, indicating that its softness is poor.

[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A binder, characterized in that: The binder comprises: 3wt% to 6.4wt% of polyethylene glycol, 2.45wt% to 18wt% of a carboxyl-containing polymer, 0.61wt% to 5wt% of a cyano-containing polymer, 0 to 9wt% of an ester-containing polymer and the remainder of a solvent.

2. The adhesive according to claim 1, characterized in that The binder comprises 3wt% to 6.2wt% of polyethylene glycol, 2.5wt% to 18wt% of a carboxyl-containing polymer, 0.63wt% to 5wt% of a cyano-containing polymer, 0 to 9wt% of an ester-containing polymer and the remainder of a solvent.

3. The adhesive according to claim 1 or 2, characterized in that: The weight average molecular weight of the polyethylene glycol is ≥500,000.

4. The adhesive according to any one of claims 1 to 3, characterized in that The carboxyl group-containing polymer includes polyacrylic acid and / or maleic acid-acrylic acid copolymer.

5. The adhesive according to any one of claims 1 to 4, characterized in that: The cyano group-containing polymer includes polyacrylonitrile.

6. The adhesive according to any one of claims 1 to 5, characterized in that: The binder includes 1.23 wt % to 9 wt % of the ester group-containing polymer.

7. The adhesive according to any one of claims 1 to 6, characterized in that: The ester-containing polymer includes at least one of polyacrylate, polyethylene glycol methyl oxalate or polycarbonate.

8. The adhesive according to any one of claims 1 to 7, characterized in that The swelling degree of the binder in the electrolyte solvent of the lithium ion battery is ≤215%, and / or the swelling degree of the binder in the electrolyte of the lithium ion battery is ≤230%.

9. A method for preparing the adhesive according to any one of claims 1 to 8, characterized in that: The preparation method of the binder comprises: A first aqueous phase solution containing the carboxyl-containing polymer and an oil phase solution containing the cyano-containing polymer are prepared respectively, the first aqueous phase solution and the oil phase solution are mixed and dispersed to form a dispersion, and the dispersion and a second aqueous phase solution containing the polyethylene glycol are mixed to prepare the binder.

10. The method for preparing the adhesive according to claim 9, characterized in that: The step of mixing and dispersing the first aqueous phase solution and the oil phase solution comprises: The first aqueous phase solution and the oil phase solution are emulsified and dispersed at a rotation speed of 1000 r / min to 5000 r / min to obtain the dispersion.

11. The method for preparing the adhesive according to claim 9 or 10, characterized in that: The step of mixing the dispersion with the second aqueous phase solution containing the polyethylene glycol comprises: The dispersion is added dropwise to the second aqueous phase solution at a dropping rate of ≤5 g / h.

12. The method for preparing the binder according to any one of claims 9 to 11, characterized in that: The ester group-containing polymer>0wt%, and the oil phase solution contains the ester group-containing polymer.

13. A negative electrode plate, characterized in that: The negative electrode plate comprises the binder as claimed in any one of claims 1 to 8, or the binder prepared by the method for preparing the binder as claimed in any one of claims 9 to 12.

14. A battery cell, characterized in that: The battery cell comprises an electrolyte and a negative electrode sheet as claimed in claim 13; Optionally, the battery cell comprises a lithium-ion battery cell.

15. The battery cell according to claim 14, characterized in that: The electrolyte includes ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and lithium hexafluorophosphate.

16. A battery, characterized in that: The battery comprises the battery cell according to claim 14 or 15.

17. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 14 or the battery according to claim 16, and the battery cell or the battery is used to provide electrical energy.